TSPAN7 promotes the migration and proliferation of lung cancer cells via epithelial-to-mesenchymal transition - Wang, Xianguo (Onco Targets Ther, 2018)
PURPOSE: To explore the effects and mechanisms of tetraspanin TSPAN7 on the progression of non-small-cell lung cancer (NSCLC) cells. PATIENTS AND METHODS: All 125 lung cancer specimens and 60 metastatic tissues were obtained from patients diagnosed with NSCLC, and we used immunohistochemistry to detect the expression of TSPAN7 in NSCLC tissues and adjacent normal tissues. Cell proliferation and invasion ability were determined by MTT, colony formation, and cell migration. The relative protein expression level was analyzed by Western blot analysis. RESULTS: Our clinical data showed that among 125 patients with lung cancer, TSPAN7 was associated with lymph node status, differentiation, tumor size, and poor prognosis. TSPAN7 knockout inhibited cell proliferation and migration. In addition, TSPAN7 increased the expression of N-cadherin in NSCLC cells by reducing the expression of E-cadherin and vimentin and promoting the cell epithelial–mesenchymal transition (EMT) process. Xenograft transplantation model confirmed the role of TSPAN7 in NSCLC metastasis. CONCLUSION: TSPAN7-mediated EMT is the key to NSCLC migration. TSPAN7 is a potential target for NSCLC therapy.